Solutions for improving the partnership between airport and airline companies - Tunčikienė, Živilė; Katinas, Romanas (Business, Management and Economics Engineering, 2020)
Purpose – For every country’s economy, air transport is strategically and vitally important. For improving the quality of air transport services provision, partnerships between airports and airlines need to be encouraged more. The application of partnerships leads to quality improvements of services provided by companies and raises the efficiency of used practices. A number of the factors, which determine the effective partnership between organisations operating in the aviation sector, is examined on the basis of specialised literature. The study addresses the question of how organisations interact with each other and what factors determine the need for partnership. Having identified common factors in the organisation’s operational interface and the need for it in the aviation sector and having analysed the practical examples of partnerships, the ways to enhance these factors are explored in order to achieve effective partnerships between airports and airlines.Research methodology – consists of comparative analysis, methods of logical analysis and abstraction, multi-criteria evaluation.Findings – The solution to the problem is expressed by identifying the factors of an effective partnership between the airports and the airlines and selecting the criteria for the assessment of the favourable effects of airport cooperation activities, and their hierarchical schemes from the positions of the airlines.Practical implications – Using multi-criteria assessment methods is easy to construct matrices of initial estimates, calculate final estimates and thus decide which airport is the most appropriate partner for an airline or vice versa.Originality/Value – A unique and, at the same time, a universal system of criteria, the application of which provides the preconditions for the development of the partnership, is created.Research limitations – The availability of data is limited to determine the reasonable values of the partnership criteria.